THE ROLE OF ANGIOTENSIN II RECEPTOR BLOCKERS IN THE FUNCTION AND MORPHOLOGY OF PLATELETS IN HYPERTENSIVE PATIENTS. (April 2021) - Konstantinou, K.; Tsioufis, K.; Kouremeti, M.; Mantzouranis, M.; Leontsinis, I.; Tolis, P.; Anastasiou, A.; Iliakis, P.; Tousoulis, D.
Abstract : Objective: Activation of platelet angiotensin receptors could potentially contribute to further progression of thrombotic events in hypertension. The aim of our study was to investigate the effect of antihypertensive therapy with ARBs on platelet function and morphology in a population of untreated hypertensive patients. Design and method: 120 untreated hypertensive patients(mean age 51 years; office blood pressure: 153/87 ± 7.3 mmHg, 55% males; 56% smokers)were divided into groups based on ARBs treatment (group 1) or no (group 2) and were prospectively followed up. Group 1 was further classified into 2 subgroups with subgroup 1 (n = 50) receiving Olmesartan and subgroup 2(n = 50)receiving Candesartan. Platelet function was assessed at baseline and at 40 days by means of a PFA-100 analyzer using epinephrine (EPI) and ADP. Time to aperture occlusion, closure time (CT), was recorded in seconds. Additionally, clotting times, mean platelet volume (MPV), vWf:Ag and fibrinogen levels were assessed. Results: At baseline, platelet activity was determined(PFA CTEPI, PFA CTADP)with no statistically significant differences between groups. At reassessment, changes in both CT- PFAEPI and CT-PFAADP were found between groups(group 1: CT-PFAEPI = 138.9 ± 22.3 sec, group 2: CT-PFAEPI = 104.9 ± 22.9 sec, group 1: CT-PFAADP = 85.5 ± 18.6 sec and group 2: CT-PFAADP = 81.5 ± 11.9 sec). However, after checking the significance of these changes (δ)it was found that only CT-PFAEPI change (δ) difference between treatment groups reached statistical significance(group 2 vs subgroup 1: δCT-PFAEPI21.8 [95% CI (2.17 – 41.4)], p = 0, 025, group 2 vs subgroup 2: δCT-PFAEPI20.7 [95% CI (1.09 – 40.3)], p = 0.035, subgroup 1 vs subgroup 2: δCT-PFAEPI 1.08[95% CI (-15.3 – 17.4)], p = NS). During follow-up, treatment with ARBs was associated with significant lowering of fibrinogen (from 341.7 ± 62.2 to 316.3 ± 61.8 mg/dl, p < 0.001), MPV levels (from 10.4 ± 0.91 to 8.8 ± 0.9fL, p < 0.001) and vWf:Ag (from 103.2 ± 6.7 to 93.8 ± 7.1)with no corresponding reductions in group 2. After multivariate analysis, CT-PFAEPI changes(δ)were significantly correlated only with ARBs(p < 0.001), irrespectively of specific drug. Conclusions: The present study indicates that treatment with ARBs contributes to downregulation of platelet activity in hypertension, suggesting that it could offer additional cardiovascular benefit in hypertensive patients.